Оцінка перспективи використання бурого вугілля на ТЕС України - Kobernik V.S. (General Energy Institute of the National Academy of Sciences of Ukraine, 2018)
The aim of this article is to determine the prospect of using brown coal at thermal power plants (TPP). For this purpose, we compare the technical-and-economic charactecteristics of power units with flame burning of bituminous and brown coal, based on different technologies (supercritical steam pressure and ultra-supercritical steam pressure), which ensure the achievement of present-day emission standards for main pollutants in accordance with Directive 2010/75/ЕU. Calculations were carried out by the average prime cost of energy generated for the life cycle (LCOE), which provides self-accounting of the source of production for the entire cycle of existence. Parameter LCOE takes into account all life-cycle costs. In order to calculate the construction of new units at thermal power plants, we used data of the International Energy Agency and program-and-information complex of the comparative estimation of cost of electric energy for the life cycle at the combustion of organic fuel in power plants, developed at the Institute of General Energy of the National Academy of Sciences of Ukraine. We analyzed the influence of type and price (according to the formula "Rotterdam +" and without it) of fuel on the average cost of electric energy for the life cycle at the introduction of new technologies of energy conversion at TPP. We may consider pulverized-coal fired power units of supercritical steam pressure with frame burning of bituminous coal with sulfur purification and nitrogen cleaning as the most economically feasible with regard for the characteristics of Ukrainian bituminous and brown coal and their value for use at the TPP. The Ukrainian brown coal has high humidity and sulfur content, hence, it needs special technologies for thermal processing. The use of brown coal at TPP is recommended after the introduction into power plants of crushing and drying facilities (e.g., microwave) to improve its quality.